MAQASID SYARIAH DAN PEMBANGUNAN HAK ASASI MANUSIA - Kurniawan, Robby (Al-Mazaahib: Jurnal Perbandingan Hukum, 2018)
Human rights, must be recognized, is a term that still debated in Islamic studies until now. This stems from the repetition statements: Human Rights (UDHR) are not born from the womb of Islam. This article attempts to find a way out of the complexity of the debate, with questions; How to build a conceptual relationship between sharia, as the concept of Islamic law, with Human Rights? The question about "relation" is more significant than "imposing" the concept of human rights on the concept of sharia. In order to create these relationships, the first thing to do is to realize that each term is a separate concept, which has its own basic deception as well. Instead, both have in common with each other. Such is the benefit and the essence of life. This point of commonality becomes a bridge that allows them to complement, and build, each other. This is where the maqasid shariah becomes inevitable in the study of Islam. Itbecomes the explanation of the connectedness of Islamic studies with other concept, in this case, Human Rights. The explanation aboutmaqasid shariah in this article is limited to the concept of maqasid Jasser Auda and Abdullahi Ahmad an-Naim. The first name is closely aligned in contemporary maqasid discourse with the system approach. While the second name, although not classified on the Maqasid figure, but has an important viewof the prospects of sharia progress.Auda offers optimization of cognition features; wholeness; openess; interelated hierarchy; multidimensionality, all of which are connected in purposefullness features. Along with that, an-Naim advocated an emphasis on the need for universal verses of Makkiyah adopted in Islamic law, other than Madaniyah. He also said, public reason is an important keyword that should not be forgotten by the law and policy formulator. In establishing the conceptual relationship between shariah and human rights, the concepts of Auda and an-Naim will be used to read three important aspects of sharia, namely, definition, source reading method, and ijtihad process to discover the truth of the law. The conclusion is that the conceptual relationship between the two can only be built by emphasizing three main points, they are 1) Changing the concept of sharia closed to the concept of open sharia with the discourse of contemporary; 2) Increase the sources of Islamic law which will be used by the Mujtahids, by input the human values as one of the things that must be considered and inspired in arrange legal products; 3) The sources of sharia should be read in such a way as to take into account the aspect of the human istidrak which cannot be detached from it.